CHALLENGES FACED BY THE FOOD AND AGRICULTURE ORGANIZATION (FAO) IN MAINTAINING FOOD SECURITY IN MYANMAR - Fakhrisa Nabilla; Chusnul Amelia Wardani (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The military coup that occurred in Myanmar in February 2021 triggered crises in various sectors, including food security. This study examines the challenges faced by the Food and Agriculture Organization (FAO) in maintaining food security amid ongoing conflict, the collapse of public services, and rising malnutrition rates. The research employs a qualitative method with a case study approach, using secondary data from reports by the FAO, World Food Programme (WFP), United Nations Office for the Coordination of Humanitarian Affairs (OCHA), and other international organizations. The findings indicate that FAO faces several major obstacles such as limited access to conflict zones, logistical disruptions due to damaged infrastructure, and inadequate funding. Furthermore, coordination with various actors, such as the Myanmar government, international donors, and local NGOs plays a crucial role in implementing food security programs. Nevertheless, restrictions imposed by the military junta remain a significant barrier to aid distribution and the recovery of the agricultural sector. This study highlights the urge for synergy among humanitarian agencies and global diplomatic pressure to open humanitarian access in Myanmar and strengthen food security for the affectedicommunities.